The Moderating Role of Independent Commissioners on the Effect of Corporate Social Responsibility (CSR) Disclosure and Chief Executive Officer (CEO) Tenure on Earnings Management - Hariyani, Diyah Santi; Juliyanti, Wiwin; Rahmiyati, Nekky; Utami, Ratna Sri (Moneta : Journal of Economics and Finance, 2025)
Earnings management is a significant concern in financial reporting, as it has the potential to mislead stakeholders and distort a company’s actual performance. This study aims to examine the effect of Corporate Social Responsibility (CSR) disclosure and Chief Executive Officer (CEO) tenure on earnings management, while also evaluating the moderating role of independent commissioners. A quantitative approach was adopted, employing multiple linear regression and Moderated Regression Analysis (MRA), based on 124 firm-year observations from 31 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2023 period. The findings reveal that CSR disclosure does not significantly influence earnings management (p = 0.089 > 0.05), suggesting that CSR activities are not effectively mitigating manipulative financial reporting. In contrast, CEO tenure has a significant positive effect on earnings management (β = 0.094; p = 0.001 < 0.05), indicating that longer-serving CEOs are more likely to engage in such practices. Furthermore, independent commissioners significantly moderate the relationship between CSR disclosure and earnings management (β = –1.689; p = 0.004), while their moderating effect on the relationship between CEO tenure and earnings management is not statistically significant (p = 0.350 > 0.05). These results emphasize the need to strengthen internal governance mechanisms to promote greater transparency in CSR reporting and to deter opportunistic behavior by executive leadership.